Digging in: lawn dissidents, performing sustainability, and landscapes of privilege. (4th July 2017) - Lebowitz, Amy; Trudeau, Dan
Abstract: 'Lawn dissidents' are people who violate norms of turfgrass yards often found in North American suburbs. This paper uses qualitative methods and engages a performance view of landscape to examine how these subjects' sustainability-oriented lawn alternatives work unintentionally to create exclusionary landscapes. As capitalism adopts environmentalism as a 'sustainability fix', niche 'green' capitalist markets allow lawn dissidents to cultivate subject positions within sustainability that ignore social justice concerns. Alongside their environmentalist concerns, lawn dissidents continue to approach land through frames that treat it as a commodity and as a signifier of cultural distinction, particularly within an elite cosmopolitan subcategory of whiteness. Nonetheless, inasmuch as lawn dissidents enact social scripts and cultivate landscapes that perform white bourgeois sensibilities around urban sustainability, the exclusionary effect of this practice is neither inevitable nor necessary. By viewing the landscapes that lawn dissidents create through the theory of the interstice, we posit an alternative direction in which sharing economies offer a more inclusive vision of sustainability in urban residential landscapes.